Application Of Information And Communication Technology In Improving Teacher Performance Competency To Develop Learning Plan At Sd Negeri 08 Pasar Surantih - Ardialis Ardialis (Fakultas Sastra Universitas Ekasakti, 2018)
Basically the task of teachers to educate, teach, train and evaluate students, so that learners can become human beings who can carry out life in harmony with his nature as human beings. related to the task of teachers in evaluating students then teachers should have the skills to teach. It is therefore necessary for the principal's role to motivate teachers to improve their performance and objectives to help teachers clearly see the purpose of education and to achieve the educational goals by fostering and developing better teaching methods and procedures. The purpose of this research is to improve teacher competence in the use of ICT, so as to improve teacher achievement and performance in competing in this globalization world. So with the use of ICT teachers are able to access and create lesson material that is better and interesting so siswapun will have better learning achievement also especially at SD Negeri 08 Pasar Surantih. The research will be applied is the School Action Research (PTS) is a type of research conducted by the principal and school supervisor. As Mulyasa pointed out that the School Action Research is an effort to improve the performance of the education system and improve school management to be productive, effective and efficient. this type of research needs to be introduced to principals and school supervisors through education and training (PTS) training. In the implementation of the PTS training, it is expected that the principal and school supervisor can: (1) understand the PTS as part of scientific research, (2) understand the meaning of private universities, (3) understand the compilation of the PTS proposal, (4) carry out and report the results of PTS conducted. According to Directorate of Tendik (2008) Step - Step PTS consists of four stages, yaituplanning (Plan), action (action), observation (observation) and reflection (reflection). The spiral cycle of the PTS stages can be as follows: The preliminary plan, prior to conducting the research the researcher formulates the problem formulation, the objectives and the action plan, including the research instrument and learning device 2. The action is done after the draft is prepared. Action is part of what will be done in Action Research School in research 3. Observation done when the teacher in bombing using a computer. The performance of teachers is strongly influenced by several factors, among others: firstly personality personality and high dedication determine the success of teachers in carrying out their duties as reflected in their attitude and actions in fostering and guiding learners. the two factors of professional development of teachers is very important because the task and its role not only provide information science but to form attitudes and souls that can survive in the era of hyperkompetition; the three factors of teaching ability of teachers is a reflection of the mastery of teachers on their competence; the four relationships and communication factors that occur in the work environment provide support for the smooth task of teachers in schools; the five factors of relationships with the community, the role of teachers in supporting school relations activities with the community can improve the understanding of the community about the goals and targets that the school wants to realize; the six disciplinary factors, A work will reap the rewards that satisfy all parties if the teacher is able to obey the specified signs through the application of discipline in carrying out their duties; the seven factors of the welfare level, provide appropriate incentives as a means of improving the welfare of teachers in order to prevent teachers from doing truancy activities by seeking additional outside to meet the needs of life; and the eight conducive working climate factors provide hope for teachers to work more calmly in line with school goals.